Development of Novel Tumor-Targeted Theranostic Nanoparticles Activated by Membrane-Type Matrix Metalloproteinases for Combined Cancer Magnetic Resonance Imaging and Therapy - Ansari, Celina; Tikhomirov, Grigory A.; Hong, Su Hyun; Falconer, Robert A.; Loadman, Paul M.; Gill, Jason H.; Castaneda, Rosalinda; Hazard, Florette K.; Tong, Ling; Lenkov, Olga D.; Felsher, Dean W.; Rao, Jianghong; et al. (Small (Weinheim an der Bergstrasse, Germany), 2014)
A major drawback with current cancer therapy is the prevalence of unrequired dose‐limiting toxicity to non‐cancerous tissues and organs, which is further compounded by a limited ability to rapidly and easily monitor drug delivery, pharmacodynamics and therapeutic response. In this report, the design and characterization of novel multifunctional “theranostic” nanoparticles (TNPs) is described for enzyme‐specific drug activation at tumor sites and simultaneous in vivo magnetic resonance imaging (MRI) of drug delivery. TNPs are synthesized by conjugation of FDA‐approved iron oxide nanoparticles ferumoxytol to an MMP‐activatable peptide conjugate of azademethylcolchicine (ICT), creating CLIO‐ICTs (TNPs). Significant cell death is observed in TNP‐treated MMP‐14 positive MMTV‐PyMT breast cancer cells in vitro, but not MMP‐14 negative fibroblasts or cells treated with ferumoxytol alone. Intravenous administration of TNPs to MMTV‐PyMT tumor‐bearing mice and subsequent MRI demonstrates significant tumor selective accumulation of the TNP, an observation confirmed by histopathology. Treatment with CLIO‐ICTs induces a significant antitumor effect and tumor necrosis, a response not observed with ferumoxytol. Furthermore, no toxicity or cell death is observed in normal tissues following treatment with CLIO‐ICTs, ICT, or ferumoxytol. These findings demonstrate proof of concept for a new nanotemplate that integrates tumor specificity, drug delivery and in vivo imaging into a single TNP entity through attachment of enzyme‐activated prodrugs onto magnetic nanoparticles. This novel approach holds the potential to significantly improve targeted cancer therapies, and ultimately enable personalized therapy regimens. The design and characterization of novel multifunctional “theranostic” nanoparticles (TNPs) is described for enzyme‐specific drug activation at tumor sites and simultaneous in vivo magnetic resonance imaging (MRI) of drug delivery. TNPs consist of iron oxide core for MR imaging, MMP‐14 cleavable peptide linker for specific activation in tumors, and a prodrug that is non‐toxic unless activated.